Corny Corn Cafe / Herman Amenhadara… [et al.] - Amenhadara, Herman; Md Karim, Dg Fatin; Hassan, Hasnah; Abdul, Norazmah; Piju, Agneas (Faculty of Business Management, Universiti Teknologi MARA, 2013)
Nowadays, there are several businesses existed in our country which compete each other. Entrepreneurship acts as the movers of the economy who involved in the business of products or services. However, the entrepreneurship has absolute right to make decision what product to be produce based on relevancy. Business might be given profit or gain losses but it depends on the entrepreneurship manage the business as well. Normally, entrepreneurship opens up business because want to get maximum profit. After we made some decision, we determined to produce Corny Com as our product. Before we made this decision, we already did various methods to identify the chance in the business field. Nevertheless, our company name is CORNY CORN CAFE which established as partners' company. We will start our company on 1 January 2013. The strategy of marketing to ensure our product can acceptable by our target market include tourist and based on our strength in service. Our marketing promotions which provide affordable price in order attract people to try our product. Overall, there no deficit in financial management while our sales profit covering the cost of operation, marketing and administration. Our location of the business will be at Suria Sabah Mall, Kota Kinabalu, Sabah.